Calibration Methods to Estimate Reference Crop Evapotranspiration and Calculated Potential Water Requirements of Olive Plant in Kermanshah Province - Husayn Mirmousavi; Hamid Panahi; Hamid Akbari; Younes Akbarzadeh (جغرافیا و پایداری محیط)
Estimating thewater requirement is among themost important factors inthedesign ofirrigationand water resources management. Todetermine thewater requirement, the evaporation-transpiration point of thereference crop should be estimated. Given that avariety of methodshave beenrecommended in this regards, selectingthe appropriate methodis a hard and complex task.Inthisstudy,fiveselectedstationsinKermanshah provinceduring theperiodbetween 17 and54yearswere used. Five methods including FAO - Penman-Monteith, Thornthwaite, Modified Blaney-Criddle, modifiedHargreavesandPenman have been used to do the needed calculations which are done based onmonthly and annualdata. Thecalculatedvalues​​ofthe potential evaporation-transpirationandtherecommendations of theWorld Meteorological Organization indicated that of the fivemethods mentioned aboveFAO - Penman-Monteithprovidesa moreaccurate estimate. Theresultsshowed thatthemonthly and annualmaximum ET0 were8.5and48.9millimeterswhich was forRavansarstationand the minimumorder of5.8and38.4mmwhich was experienced in Kangavarstation, and finally it showed that the maximumannualwater requirementforRavansarstationis923.3mm.